Ecological Niche Structure and the Interactive Role of Leaf‐Nosed Bats (Chiroptera: Phyllostomidae) Within Frugivory Networks: Another Dimension of the Niche Centroid Hypothesis - Alejandro R. Villa; Diana M. Ochoa‐Sanz; Fabricio Villalobos; M. Cristina MacSwiney G.; Octavio Rojas‐Soto; Wesley Dáttilo (Ecology Letters, 2025)
Numerous studie have explored the factors shaping species' roles within ecological networks, but little is known about how these roles vary across communities. Climatic niche suitability has been proposed as a key driver of this variation, yet evidence is scarce, especially for bats. Here, we tested whether bat populations in areas with higher climatic suitability play more interactive roles within frugivory networks in the American tropics. Our first analyses revealed positive associations for four species and a negative one for another; however, these relationships were no longer statistically significant after correcting for multiple comparisons. Despite this, effect sizes and relationship directions remained consistent, suggesting meaningful ecological patterns. This study offers a new framework for studying how climatic factors influence species' roles in networks. Our findings provide insights into how environmental factors shape biotic interactions and highlight the importance of climate as a driver of community dynamics.